Investigation of Gas Transportation in Main Pipelines - Gurbanov, A.N.; Sardarova, I.Z.; Aliyev, J.R.; Nurmammadova Huseynova, S.B. (Herald of Azerbaijan Engineering Academy, 2025)
The separation of liquid and mechanical solid particles from the transported gas and their deposition in the relief depressions of the pipeline lead to a violation of the regularity of the flow, which is the reason for reducing the service life of the pipeline and process equipment. In addition, condensate and mechanical solid particles contained in the gas supplied to the enterprises of the processing industry create difficulties in the normal operation of the process equipment. To separate and collect condensate and solid mechanical particles during gas transportation, the direction of the gas flow into the collection tank is changed by installing a tank for collecting condensate at the beginning and end of the pipeline in the direction of flow and installing a triangle in front of the tank, then a knee based on the specific gravity and mechanical energy of the separated mechanical particles of solids and condensate collected from the gas flow into the tanks due to the difference in their weight.